Digital physical culture and health technologies in the aspect of improving the working capacity of workers (foreign and Russian experience) - N. V. Filonenko (Путеводитель предпринимателя)
The article examines the positive aspects of foreign and Russian experience in physical culture and health–improving work with workers. Attention is focused on the economic feasibility of using digital physical culture and health–improving technologies in the management of organizations, through which, according to the author, it is possible to organize physical education during the working day not only for large corporations, but also for small firms, which will have a positive effect on improving the efficiency of workers and labor productivity. It also emphasizes the key role of municipal–private partnerships in the creation and implementation of projects related to corporate sports.